Runoff generating processes in adjacent tussock grassland and pine plantation catchments as indicated by mean transit time estimation using tritium - M. K. Stewart; B. D. Fahey (Hydrology and Earth System Sciences, 2010)
The east Otago uplands of New Zealand's South Island have long been studied because of the environmental consequences of converting native tussock grasslands to other land covers, notably forestry and pasture for stock grazing. Early studies showed that afforestation substantially reduced annual water yield, stream peak flows, and 7-day low flows, mainly as a consequence of increased interception. Tritium measurements have indicated that surprisingly old water is present in catchments GH1 and GH2, and the small headwater wetland and catchment (GH5), and contributes strongly to baseflow. The data have been simulated assuming the presence of two types of water in the baseflow, young water from shallow aquifers connecting hillside regolith with the stream, and old water from deep bedrock aquifers, respectively. The mean transit time of the young water is approximately one month, while that of the old water is 25–26 years as revealed by the presence of tritium originating from the bomb-peak in NZ rainfall in late 1960s and early 1970s. Such a long transit time indicates slow release from groundwater reservoirs within the bedrock, which constitute by far the larger of the water stores. Comparison of the results from catchments GH1 (tussock) and GH2 (pine forest) suggests that about equal quantities of water (85 mm/a) are contributed from the deep aquifers in the two catchments, although runoff from the shallow aquifers has been strongly reduced by afforestation in GH2. This study has revealed the presence of a long transit time component of water in runoff in a catchment with crystalline metamorphic bedrock.